The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2023
DOI: 10.1002/smll.202206169
|View full text |Cite
|
Sign up to set email alerts
|

Plastic Deformation in a Molecular Crystal Enables a Piezoresistive Response

Abstract: Organic materials are promising candidates for the development of efficient sensors for many medicinal and materials science applications. Single crystals of a small molecule, 4‐trifluoromethyl phenyl isothiocyanate (4CFNCS), exhibit plastic deformation when bent, twisted, or coiled. Synchrotron micro‐focus X‐ray diffraction mapping of the bent region of the crystal confirms the mechanism of deformation. The crystals are incorporated into a flexible piezoresistive sensor using a composite constituting PEDOT: P… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 58 publications
1
6
0
Order By: Relevance
“…65 Notably, it was found that the mechanisms varied significantly even for molecules that have similar crystal structures, demonstrating that bending mechanisms are not universal, but rather have subtle differences depending on the intermolecular interactions and crystal packing arrangements. 93 Altogether, these results confirm that there is no universal mechanism of bending, and each structure should be studied by using direct methods that provide information on the structural perturbations with atomic-scale resolution.…”
Section: Direct Evidence For the Mechanisms Of Crystal Bendingsupporting
confidence: 53%
“…65 Notably, it was found that the mechanisms varied significantly even for molecules that have similar crystal structures, demonstrating that bending mechanisms are not universal, but rather have subtle differences depending on the intermolecular interactions and crystal packing arrangements. 93 Altogether, these results confirm that there is no universal mechanism of bending, and each structure should be studied by using direct methods that provide information on the structural perturbations with atomic-scale resolution.…”
Section: Direct Evidence For the Mechanisms Of Crystal Bendingsupporting
confidence: 53%
“…The device developed by Hasija et al 64 characterizes the plastic deformation in 4-trifluoromethyl phenyl isothiocyanate (4-trifluoromethyl phenyl isothiocyanate 4CFNCS) crystals as described in Fig. 4(c).…”
Section: Wearable Pressure Sensorsmentioning
confidence: 99%
“…However, during the twisting process, the twisting forces (T) are tangential to the cross-section of crystals (Figure S19b). 36 Because the molecules are stacked along the long axis to form π-stacked columns by π•••π interactions, the twisting forces are also tangential to π•••π interactions and not coplanar with each other. However, other interactions connecting the π-stacked columns are almost coplanar with the twisting forces.…”
Section: Multiple Mechanical Flexibilities and Their Mechanismsmentioning
confidence: 99%